Addition of roxadustat to erythropoiesis‐stimulating agent (ESA) effectively corrects ESA‐hyporesponsive anaemia in patients on peritoneal dialysis. (28th May 2022) - Dai, Shuqi; Chen, Yun; Hao, Chuanming; Ge, Xiaolin; Xie, Qionghong; Shang, Da; Zhu, Tongying
Abstract: What Is Known and Objective: Erythropoiesis‐stimulating agent (ESA) hyporesponsiveness is an important cause for the undertreatment of anaemia. A decrease in haemoglobin (Hb) levels was observed during the initial stage of the conversion from ESA to roxadustat. The study aims to investigate the effectiveness and safety of adding roxadustat to an ESA for the treatment of ESA‐hyporesponsive anaemia in patients on peritoneal dialysis (PD). Methods: Patients on PD with ESA‐hyporesponsive anaemia were enrolled from January 2020 to April 2020 with a 24‐week follow‐up period. Patients were treated with roxadustat at a starting dose of 50 or 100 mg thrice weekly without changing the ESA dose. Roxadustat and ESA dose adjustments were made as needed to maintain Hb levels within 11.0 to 13.0 g/dl. Efficacy outcomes and safety were assessed. Results and Discussion: Nine patients were recruited in the study. Both the cumulative responsive rate and maintenance rate of Hb > 11 g/dl were 100%. Six patients required ESA dose reduction from ≥15, 000 UI/week to ≤7000 IU/week at week 24. No drug‐related severe adverse events were observed in this study. What Is New and Conclusion: The addition of roxadustat effectively and smoothly corrected anaemia in patients who were hyporesponsive to ESA, and permitted reduction of the ESA dose. Abstract : The addition of roxadustat effectively and smoothly corrected anaemia in patients who were hyporesponsive to ESA, and permitted reduction of the ESA dose.